Update on the Financing of the Fund's Concessional Assistance and Debt Relief to Low-Income Member Countries. (Policy Papers; Policy Paper, 2014)
New commitments under programs supported by the Poverty Reduction and Growth Trust (PRGT) amounted to SDR 0.6 billion during the first nine months of 2014, and disbursements on existing arrangements amounted to about SDR 0.3 billion through end-August. While this level of demand is low by historical standards, new commitments for 2014 as a whole could still exceed SDR 1 billion. These projections are, however, subject to considerable uncertainty regarding progress with ongoing program negotiations.